Peningkatan Produktifitas Kerja Melalui Budaya Kerja dan Motivasi Kerja Pada PT Pelita Air Service Tangerang - Oktiani, Nurvi; Winarno, Slamet Heri (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2020)
This study aims to analyze and test the relationship or influence of work culture and work motivation on the work productivity of airline employees of PT Pelita Air Service Tangerang. Respondents in this study amounted to 100 employees from various parts of the company using purposive sampling techniques. The research design uses quantitative research survey methods, interviews and questionnaires. Data collection was carried out by distributing questionnaires using a Likert scale. The analysis technique uses descriptive analysis and inferential analysis using the correlation regression analysis method. The results showed that work culture and work motivation had a positive and significant effect on work productivity by 71% while 29% were influenced by other factors.